2006
DOI: 10.1243/095765005x69189
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional unsteady investigation of HP turbine stages

Abstract: This article deals with a three-dimensional unsteady numerical simulation of the unsteady rotor—stator interaction in a HP turbine stage. The numerical approach consists of a computational fluid dynamics (CFD) parallel code, based on an upwind total variation diminishing finite volume approach. The computation has been carried out using a sliding plane approach with hybrid unstructured meshes and a two-equation turbulent closure. The turbine rig under investigation is representative of the first stage of aeron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The stator-rotor rows are matched through a sliding plane approach, properly developed for general unstructured grids [10] and widely assessed for the aero-thermal investigation of HP transonic turbines [11]. A reduced count-ratio approach is applied gathering an exact periodicity among the rows.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The stator-rotor rows are matched through a sliding plane approach, properly developed for general unstructured grids [10] and widely assessed for the aero-thermal investigation of HP transonic turbines [11]. A reduced count-ratio approach is applied gathering an exact periodicity among the rows.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The conventional turbulence models offer a good balance between grid resolution requirement and flow field complexity; on the other hand, the large eddy simulation is still prohibitive and probably too detailed to be used for engineering design purposes [20]. Zhou et al [21] used several turbulence models such as Spalart-Allmaras, standard k-ε, kω-SST, and transition kω-SST in studying the effect of the trailing edge of ultrahigh lift lp turbine blades and showed that the two last models provided a good prediction of aerodynamic performance compared with experiments.…”
Section: Turbulence Modelmentioning
confidence: 99%